If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -10 = -8 + 8x Reorder the terms: -10 + 6x = -8 + 8x Solving -10 + 6x = -8 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -10 + 6x + -8x = -8 + 8x + -8x Combine like terms: 6x + -8x = -2x -10 + -2x = -8 + 8x + -8x Combine like terms: 8x + -8x = 0 -10 + -2x = -8 + 0 -10 + -2x = -8 Add '10' to each side of the equation. -10 + 10 + -2x = -8 + 10 Combine like terms: -10 + 10 = 0 0 + -2x = -8 + 10 -2x = -8 + 10 Combine like terms: -8 + 10 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| x(a-b)=d+c | | 200=n+6(8+3n) | | -3/8x-4=1/8x-5 | | D=Ty | | 6*5+3=y | | 5g-2h=-5 | | 3x+9=7x-5 | | 122=9/5c+32 | | 4w+12(w-1)=36 | | 2(x+5)+3(x-5)=180 | | -5b=-8 | | 4x^2+8x=320 | | 21d-4=-67 | | -5(2t-3)+2t=8t-6 | | 8-2x+8+1=5x+5+1 | | 3*x-4=11 | | 3(4y-21)=7 | | 0.25x+7=0.33x-8 | | loge(x^2)-2=0 | | -2xy=-3 | | 15-.75z=13-.50z | | -6+3v+v=6 | | r+26-32r=-41 | | 8x^2-16x-8=0 | | -3(4t-5)+2t=6t-4 | | 2x+[5x(-2x-3x)]= | | 6x-10=2x-2 | | X=4x+8x | | 11-4n=17 | | 3x=11+49 | | 10=h-5g | | 2.2-7.3= |